2015
DOI: 10.1038/jid.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Cannabinoid-Induced Cytotoxic Autophagy to Drive Melanoma Cell Death

Abstract: Although the global incidence of cutaneous melanoma is increasing, survival rates for patients with metastatic disease remain <10%. Novel treatment strategies are therefore urgently required, particularly for patients bearing BRAF/NRAS wild-type tumors. Targeting autophagy is a means to promote cancer cell death in chemotherapy-resistant tumors, and the aim of this study was to test the hypothesis that cannabinoids promote autophagy-dependent apoptosis in melanoma. Treatment with Δ(9)-Tetrahydrocannabinol (THC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 41 publications
4
128
1
3
Order By: Relevance
“…Thus, THC binds cannabinoid receptors, which leads to the stimulation of sphingolipid synthesis de novo and the subsequent activation of an ER stress-related signaling route that involves the up-regulation of the transcriptional co-activator nuclear protein 1 (Nupr1, also named p8) and its effector the pseudo-kinase tribbles homolog 3 (TRIB3) (Armstrong et al, 2015;Blazquez et al, 2004;Carracedo et al, 2006a;Carracedo et al, 2006b;Galve-Roperh et al, 2000;Gomez del Pulgar et al, 2002;Velasco et al, 2012). The stimulation of this pathway promotes in turn autophagy via TRIB3-mediated inhibition of the AKT/ mTORC1 axis (Salazar et al, 2009;Salazar et al, 2013).…”
Section: Cannabinoids Induce Cancer Cell Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, THC binds cannabinoid receptors, which leads to the stimulation of sphingolipid synthesis de novo and the subsequent activation of an ER stress-related signaling route that involves the up-regulation of the transcriptional co-activator nuclear protein 1 (Nupr1, also named p8) and its effector the pseudo-kinase tribbles homolog 3 (TRIB3) (Armstrong et al, 2015;Blazquez et al, 2004;Carracedo et al, 2006a;Carracedo et al, 2006b;Galve-Roperh et al, 2000;Gomez del Pulgar et al, 2002;Velasco et al, 2012). The stimulation of this pathway promotes in turn autophagy via TRIB3-mediated inhibition of the AKT/ mTORC1 axis (Salazar et al, 2009;Salazar et al, 2013).…”
Section: Cannabinoids Induce Cancer Cell Deathmentioning
confidence: 99%
“…9 upstream of apoptosis in the mechanism of cannabinoid-induced cell death (Armstrong et al, 2015;Salazar et al, 2009;Vara et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown the ability of cannabinoids to affect cellular signalling pathway/s essential for cell survival and growth Kogan, 2005). Some studies have also demonstrated and suggested the involvement of autophagy in the mechanism of cannabinoidinduced cytotoxicity (Armstrong et al 2015;Vara et al, 2011;McAllister et al, 2015).…”
Section: Anti-tumour Effects Of Cannabinoidsmentioning
confidence: 99%
“…This group went on to further demonstrate that CB 1 -selective and CB 2 -selective receptor agonists induced autophagic cell death in part through the initial induction of the ROS sensor AMP-activated protein kinase (AMPK) (Dando et al, 2013). More recently, CBD has been shown to enhance the ability of THC to inhibit tumor progression in mice bearing BRAF wildtype melanoma xenografts through activation of autophagy-mediated cell death (Armstrong et al, 2015). …”
Section: Non-psychoactive Plant-derived Cannabinoids As Inhibitorsmentioning
confidence: 99%